Development of e-comic based learning media in civics subjects to develop the character of student at Public Junior High School 3 Magetan, Indonesia - Harmawati, Yuni; Handayani, Hanni; Nuswantari , Nuswantari (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2024)
Pancasila and citizenship education is one of the subjects that can grow the character of students. Pancasila and civic education teachers have an important role in educating students in the midst of the influence of this technological age. The problem that occurs is that Pancasila and civic education learning is not liked and in demand by students because the available material is quite boring, because teachers only apply the lecture method and the media used is still in the form of school package books. The researcher developed e-comic-based digital learning media  in Pancasila and civic education learning. The purpose of this study is to test the feasibility of media as a means to grow the character of students at Public Junior High School 3 Magetan. The type of research used is Research and Development (RnD) with the ADDIE (Analalys, Design, Development, Implementation, Evaluation) research model. The data analysis technique used is quantitative to calculate the results of media feasibility from learning experts and the results of practicality of student responses. Qualitative data to analyze problems and analyze quantitative results. The result of this research and development is that the researcher succeeded in obtaining media feasibility from learning experts by 75% with the feasible category and obtaining media practicality by 75.35% with the very practical category. Thus, based on the results obtained, after reading the stories in the e-comic, students can cultivate the character of mutual cooperation and tolerance towards students.